Growing a sustainable city? : the question of urban agriculture - Rosan, Christina; Pearsall, Hamil; University of Toronto. Press (Toronto : University of Toronto Press, 2017)
Growing a Sustainable City? offers a critical analysis of the development of urban agriculture policies and their role in making post-industrial cities more sustainable. Christina Rosan and Hamil Pearsall's intriguing and illuminating case study of Philadelphia reveals how growing in the city has become a symbol of urban economic revitalization, sustainability, and - increasingly - gentrification. Their comprehensive research includes interviews with urban farmers, gardeners, and city officials, and reveals that the transition to "sustainability" is marked by a series of tensions along race, class, and generational lines. The book evaluates the role of urban agriculture in sustainability planning and policy by placing it within the context of a large city struggling to manage competing sustainability objectives. They highlight the challenges and opportunities of institutionalizing urban agriculture into formal city policy. Rosan and Pearsall tell the story of change and growing pains as a city attempts to reinvent itself as sustainable, livable, and economically competitive.--AMAZON.
Introduction : The dilemma of urban agriculture -- The rise of urban agriculture as a short-term strategy (1893-1980) -- The agendas of urban agriculture at its peak (1990-2000s) -- The politics of urban agriculture in sustainability planning -- "New growers" making sense of their role -- Putting growing in the city in perspective -- Transitioning towards a sustainable future?
Includes bibliographical references (pages 163-185) and index.
Keywords: Urban agriculture; Urban agriculture -- Pennsylvania -- Philadelphia -- Case studies; Sustainable agriculture; Sustainable agriculture -- Pennsylvania -- Philadelphia -- Case studies; Sustainable urban development; Sustainable urban development -- Pennsylvania -- Philadelphia -- Case studies